2016
DOI: 10.1088/0953-8984/28/50/505101
|View full text |Cite
|
Sign up to set email alerts
|

Universal shape characteristics for the mesoscopic polymer chain via dissipative particle dynamics

Abstract: In this paper we study the shape characteristics of a polymer chain in a good solvent using a mesoscopic level of modelling. The dissipative particle dynamics simulations are performed in 3D space at a range of chain lengths N. The scaling laws for the end-to-end distance and gyration radius are examined first and found to hold for [Formula: see text] yielding a reasonably accurate value for the Flory exponent ν. Within the same interval of chain lengths, the asphericity, prolateness and some other shape chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 47 publications
5
16
0
1
Order By: Relevance
“…This correlates well with the findings that a linear chain within the DPD enters scaling regime at moderate values of N ∼ 8 − 10. [41] It is also interesting to note that the Daoud-Cotton ansatz provides the result that is very close to our simulations at f > 10, following the discussion in ref. [34] that this ansatz is valid for the case of a rather large number of branches f. Let us now switch to the p A (f ) ratio for a star defined in Equation (3), the results obtained in this study are shown in Figure 3, where they are compared to the simulations by Batoulis and Kremer [23] and the results for the Gaussian model.…”
Section: Comparison Of the Dissipative Particle Dynamics Results Withsupporting
confidence: 87%
See 3 more Smart Citations
“…This correlates well with the findings that a linear chain within the DPD enters scaling regime at moderate values of N ∼ 8 − 10. [41] It is also interesting to note that the Daoud-Cotton ansatz provides the result that is very close to our simulations at f > 10, following the discussion in ref. [34] that this ansatz is valid for the case of a rather large number of branches f. Let us now switch to the p A (f ) ratio for a star defined in Equation (3), the results obtained in this study are shown in Figure 3, where they are compared to the simulations by Batoulis and Kremer [23] and the results for the Gaussian model.…”
Section: Comparison Of the Dissipative Particle Dynamics Results Withsupporting
confidence: 87%
“…Providing some answers in refs. [40][41][42], here we also show that the method describes adequately the excluded volume effect in the case of dense star with a relatively large number of arms.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Як виявилося, зокрема й у результатi наших до-слiджень, унiверсальним степеневим законам пiдля-гають й iншi спостережуванi, що описують конформа-цiйнi властивостi полiмерних ланцюгiв та iнших мак-ромолекулярних утворень, складних як за топологiєю (полiмернi сiтки та зiрки), так i за хiмiчним складом (кополiмери та кополiмернi сiтки) [26,27]. Щобiльше, унiверсальною виявляється i форма таких утворень [28]. Деякi нашi результати в цiй дiлянцi, а також ре-зультати дослiдження конформацiйних властивостей полiмерiв у пористому середовищi [29][30][31] наведенi в роздiлах V-VIII.…”
Section: складнI полIмернi макромолекулиunclassified